Analysis Of Beginning Reading Difficulties Among Second-Grade Elementary School Students - Siti Elva Susanti; Ahmad Ahmad; Sri Marlia Puteri (Journal of Education and Learning Sciences, 2025)
This study aimed to analyze the beginning reading skills of second-grade students, identify the difficulties they encountered, and describe the efforts undertaken to address those difficulties. The study employed a qualitative descriptive design involving a second-grade teacher and students as research participants. Data were collected through observation, semi-structured interviews, and documentation. Data analysis consisted of data collection, data reduction, data display, and conclusion drawing, while data credibility was established through source, method, and time triangulation. The findings indicated that the students' beginning reading skills were generally at a moderate level. Most students were able to recognize letters, produce letter sounds, read syllables and words, and read simple sentences. However, some students continued to experience difficulties distinguishing visually similar letters, reading fluently, reading without spelling out words, and demonstrating confidence when reading aloud. The main challenges included low interest in reading, limited self-confidence, insufficient parental assistance and support at home, limited instructional media, and insufficiently varied teaching methods. To address these challenges, the teacher provided targeted support, implemented a staged reading approach, utilized instructional media and educational games, conducted regular reading practice, involved parents, and provided praise and encouragement. The study concludes that beginning reading skills are influenced by both internal and external factors. Therefore, sustained collaboration among teachers, students, and parents is essential to optimize the development of students' foundational reading skills.